From outdated to outstanding: an institution’s journey in reforming the dental materials science curriculum and lessons learned - Lin, Galvin Sim Siang; Foong, Chan Choong; Kumaresan, Ramesh (Springer Nature, 2024)
Background: The Dental Materials Science (DMS) course within Malaysian undergraduate dental education has traditionally been taught in isolation, with a relatively stagnant delivery mode. Recent shifts in national dental competency standards have necessitated substantial reform in the DMS curriculum. This study aims to outline the journey of a local dental institute in developing and implementing a competency-based DMS curriculum. Methods: A faculty curriculum task force was established to oversee the curriculum reform process. The reform was guided by a "bottom-up" approach using the five-step curriculum reform model: (1). Curriculum mapping, (2). Comprehensive needs assessment, (3). Clear learning objectives and outcomes, (4). Curriculum development and implementation, and (5). Continuous evaluation and improvement. Results: Step 1 revealed the need to reduce content repetition and improve alignment with the new competency standards. Step 2 identified the need to include advanced materials, integrate theoretical and clinical aspects, and enhance teaching methods. The new curriculum included 25 relevant topics. Step 3 established three course learning outcomes, while Step 4 integrated DMS content horizontally and vertically across the curriculum, introduced innovative teaching methods, and diversified assessment methods. Step 5 ensured ongoing curriculum monitoring, with both short-term and long-term evaluations planned. Conclusion: The curriculum reform process represents a significant advancement in dental materials science while addressing challenges and aligning the curriculum with national standards. Ongoing evaluation, adaptability, interdisciplinary collaboration, and international engagement are essential for further improvements. This journey serves as a valuable reference for educators seeking to update their DMS curricula.